A new weighted fuzzy programming model for supplier selection and order allocation in the food industry. (3rd February 2020) - Kaviani, Mohamad Amin; Peykam, Alireza; Khan, Sharfuddin Ahmed; Brahimi, Nadjib; Niknam, Raziyeh
Abstract : Purpose: The purpose of this paper is to develop a combined intuitionistic fuzzy analytic hierarchy process (IFAHP) and fuzzy multi-objective optimization approach to select suppliers and allocate the orders to them in the bottled water production context. Design/methodology/approach: First, the primary weights of criteria associated with the supplier selection problem are calculated using the IFAHP technique. Then a fuzzy multi-objective optimization model is developed to allocate the appropriate amount of orders to each supplier. Findings: The proposed methodology has been successfully implemented in the case of an Iranian food company in its bottled water factory. Results demonstrate our model is capable of practically handling the uncertainty in DMs' preference that leads to effective and efficient supplier selection and order allocation decisions. Originality/value: The authors develop a novel hybrid decision-making tool to tackle the uncertainty in decision-makers' opinions with a demonstrated applicability and some promising outcomes in efficiently allocating the order quantity to suppliers in the area of bottled water production.